2014
DOI: 10.20529/ijme.2014.048
|View full text |Cite
|
Sign up to set email alerts
|

Teaching of public health ethics in India: a mapping exercise

Abstract: Public health ethics has been receiving increasing attention in recent years. Frequently, public health practitioners have to confront complex decisions, with numerous and often conflicting ethical implications. The objective of this study was to obtain information on the teaching of public health ethics in India by making a detailed examination of the public health and community medicine curricula. The specific areas of interest included the content and structure of the courses and electives available to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Thus, PHE education should ideally be adapted to students' contexts and needs, as well as to local social objectives. Regardless of the method used, actively involving students seems to be one of the most important components of PHE training (Pati et al 2014). To this one can add the need to actively involve PH educators and SPH in making PHE broadly relevant to students, and an important part of their training.…”
Section: The Content and Educational Methods Of Ethics Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, PHE education should ideally be adapted to students' contexts and needs, as well as to local social objectives. Regardless of the method used, actively involving students seems to be one of the most important components of PHE training (Pati et al 2014). To this one can add the need to actively involve PH educators and SPH in making PHE broadly relevant to students, and an important part of their training.…”
Section: The Content and Educational Methods Of Ethics Educationmentioning
confidence: 99%
“…We identified only one study, conducted in India (Pati et al 2014), and its authors found no standardization of curriculum nor any consensus about ethics education in public health. Concerning MPH programs offered by 31 institutions in India, only 11 had a dedicated module for ethics (elective and compulsory).…”
Section: Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare ethics education in India is making progress, but it is still in its infancy. A recent mapping exercise of teaching of public health ethics revealed that little attention is paid to ethics training in medical education (Pati et al 2014). In medical and nursing curricula, some attention is often given to healthcare ethics, but this is not always the case and does not seem to properly prepare the students for the ethical difficulties that they will encounter in medical and nursing practice.…”
Section: Healthcare Ethics In Medical Education In Indiamentioning
confidence: 99%